The influence of magnetised electron transport on thermal self-focusing and channelling of nanosecond laser beams. (May 2016) - Read, Martin; Kingham, Robert; Bissell, John
Abstract: The propagation of a nanosecond IR laser pulse through an under-dense (0.01 — 0.1ncr ) magnetised laser-plasma is considered. The interplay between magnetised transport, B-field evolution and plasma hydrodynamics in the presence of a dynamically evolving beam are investigated by means of a paraxial wave solving module coupled to CTC, a 2D MHD code including Braginskii electron transport and IMPACT, a 2D implicit Vlasov-Fokker-Planck (VFP) code with magnetic fields. Magnetic fields have previously been shown to improve density channel formation for plasma waveguides however fluid simulations presented here indicate that Nernst advection can result in the rapid cavitation of magnetic field in the laser-heated region resulting in beam defocusing. Kinetic simulations indicate that strong non-local transport is present leading to the fluid code overestimating heat-flow and magnetic field advection and resulting in the recovery of beam channelling for the conditions considered.